Perancangan Desain Infografis Dan Kampanye Tentang Bahaya Rokok Bagi Pelajar Tingkat Menengah Di Indonesia - Wahid, Ahmad; Setyanto, Daniar Wikan (LPPM STIKI Malang, 2025)
The prevalence of smoking among Indonesian teenagers continues to rise, posing a serious public health issue. Data from the Indonesian Health Survey and the Global Youth Tobacco Survey indicate that 7.4% of adolescents aged 10-18 are active smokers, with an increasing trend in electronic cigarette use. Social influences, advertising exposure, and a lack of engaging educational content contribute to this behavior, highlighting the need for a more effective communication strategy. This study aims to design effective infographics and a digital campaign to raise awareness of the dangers of smoking among secondary school students. The infographics serve as engaging and easily understood visual communication tools, intended to enhance awareness and shift students' perceptions of smoking. A qualitative research approach was used, employing literature studies and framing analysis to identify impactful visual communication strategies for students. The design results show that infographics featuring simple illustrations, and contrasting colors enhance students' understanding and engagement in the anti-smoking campaign. This campaign is expected to encourage positive behavioral changes, reduce smoking prevalence among students, and support efforts to create a smoke-free environment.